Shared spatial and temporal principles govern connectome dynamics across timescales - Thomas H. Alderson; Suhnyoung Jun; Jonathan Wirsich; Maximillian Kirichenko Egan; Samar Wagih ElSayed; Sophia A. Giakas; Parham Mostame; Jeremy Harper; Anne-Lise Giraud; Stephen M. Malone; William G. Iacono; Sanmi Koyejo; et al. (Proceedings of the National Academy of Sciences, 2026)
While the brain processes information at various speeds, little is known about how the functional connectome can concurrently support multiple speeds in parallel. FMRI and electrophysiological modalities have been used to study connectome dynamics at slow and fast speeds, respectively. But it is often implicitly assumed that these modalities capture the same underlying neural processes, with fMRI doing so through a low-pass temporal filter. However, recent work suggests the alternative possibility that connectome dynamics comprise distinct processes operating at multiple timescales. If such multiscale connectivity processes indeed coexist, a key question is whether their patterns and sequences are organized on the basis of shared regularities, i.e., common spatial and temporal principles. In simultaneous human fMRI and source-localized EEG, we investigated the connectome’s foundational constituents—the instantaneous coactivation patterns—across six timescales of neural activity, from infraslow through γ-band. We found streams of recurrent coactivation patterns, or states, that operate in parallel and asynchronously across timescales, thereby forming a timescale-overarching spatial principle. These states also occurred in highly similar sequences at all timescales, revealing a timescale-overarching temporal principle. Together, these findings indicate that the connectome comprises multiple dynamic streams operating in parallel at distinct speeds, from tens of milliseconds to seconds, rather than a single stream filtered by each modality’s temporal resolution. Spatial and temporal principles that span these streams enable their integration into a unified system. Consequently, research on human behavior and mental disorders should account for the full range of the connectome’s timescales.